One‐Component Dual Actuation: Poly(NIPAM) Can Actuate to Stable 3D Forms with Reversible Size Change. Issue 44 (22nd September 2016) - Liu, Li; Ghaemi, Ali; Gekle, Stephan; Agarwal, Seema
Abstract : A rare example of a one‐component dual actuator is provided, which displays irreversible change in shape by rolling on contact with water and reversible size change on changing the temperature. The actuator has a bilayer structure with aligned and randomly oriented fibers of poly( N ‐isopropyl acrylamide). A combination of anisotropic E modulus and temperature dependent swelling/shrinkage provides the dual actuation.